T T ¯ $$ \overline{T} $$ deformation in SCFTs and integrable supersymmetric theories - Stephen Ebert; Hao-Yu Sun; Zhengdi Sun (Journal of High Energy Physics, 2021)
Abstract We calculate the S $$ \mathcal{S} $$ -multiplets for two-dimensional Euclidean N $$ \mathcal{N} $$ = (0, 2) and N $$ \mathcal{N} $$ = (2, 2) superconformal field theories under the T T ¯ $$ \overline{T} $$ deformation at leading order of perturbation theory in the deformation coupling. Then, from these N $$ \mathcal{N} $$ = (0, 2) deformed multiplets, we calculate two- and three-point correlators. We show the N $$ \mathcal{N} $$ = (0, 2) chiral ring’s elements do not flow under the T T ¯ $$ \overline{T} $$ deformation. Specializing to integrable supersymmetric seed theories, such as N $$ \mathcal{N} $$ = (2, 2) Landau-Ginzburg models, we use the thermodynamic Bethe ansatz to study the S-matrices and ground state energies. From both an S-matrix perspective and Melzer’s folding prescription, we show that the deformed ground state energy obeys the inviscid Burgers’ equation. Finally, we show that several indices independent of D-term perturbations including the Witten index, Cecotti-Fendley-Intriligator-Vafa index and elliptic genus do not flow under the T T ¯ $$ \overline{T} $$ deformation.